Security management for sports and special events : an interagency approach to creating safe facilities - Hall, Stacey A.; Cooper, Walter E.; Marciani, Lou; McGee, James A. (Champaign, IL : Human Kinetics)
The book presents a systematic approach to stadium and venue security. It deals specifically with natural disasters, terrorism, crowd control problems, and other large-scale threats. This practical resource offers detailed guidance in improving the quality, coordination, and responsiveness of security protocols in their facilities.--[book cover]